Weighing the relative importance of short-term versus long-term outcomes when comparing surgery versus stereotactic body radiation therapy (SBRT) for early-stage non-small cell lung cancer - Speicher, Paul J.; D’Amico, Thomas A. (Journal of Thoracic Disease, 2018)
Lung cancer continues to be the leading cause of cancer death in the United States, with an estimated 234,030 new cases and 154,050 deaths expected in 2018 alone (1).